Analysis of batch and repeated fedbatch productions of Candida utilis cell mass using mathematical modeling method - Gao, Ling; Lin, Yutian; Liu, Guoli; Lin, Huibin; Lin, Jianqiang (Electronic Journal of Biotechnology, 2013)
Background: Candida utilis is widely used in bioindustry, and its cell mass needs to be produced in a cost effective way. Process optimization based on the experimental results is the major way to reduce the production cost. However, this process is expensive, time consuming and labor intensive. Mathematical modeling is a useful tool for process analysis and optimization. Furthermore, sufficient information can be obtained with fewer experiments by using the mathematical modeling, and some results can be predicted even without doing experiments. Results: In the present study, we performed the mathematical modeling and simulation for the cell mass production of Candida utilis based on limited batch and repeated fedbatch experiments. The model parameters were optimized using genetic algorithm (GA), and the processes were analyzed. Conclusions: Taken together, this newly developed method is efficient, labor saving and cost effective.